Bundle-branch Block in Acute Myocardial Infarction. Issue 5636 (11th January 1969) - Hunt, David; Sloman, Graeme
Abstract : Bundle-branch block was present in 41 out of 415 patients admitted to a coronary care unit with acute myocardial infarction and was associated with more severe clinical infarction and an overall mortality of 56%. It is probable that permanent bundle-branch block develops soon after infarction and that most of the patients with permanent block have had clinically severe infarction. Bundle-branch block developing during observation is usually transient, and the later it develops the sooner it resolves. Analysis of the arrhythmias and clinical course of the patients suggests that those with bundle-branch block and shock and those in whom bundle-branch block is present on admission may benefit from the use of a demand pacemaker attached to a transvenous pacemaker catheter, though the dividends of pacing may be small and the risks of the procedure significant. Post-mortem examination of 17 hearts showed extensive infarction, usually involving the septum, and severe coronary artery disease.